Radical Turn: The Case of Front Persaudaraan Islam (Neo-FPI) in Indonesia - Taufiq, Firmanda; Tsauro, Ahalla (Journal of Asian Wisdom and Islamic Behavior, 2024)
In the last decade, a religious conservatism group of Front Pembela Islam (FPI) was notoriously controversial due to series of anti-government protests, harsh approaches as well as opposing state constitution which led to this group disbandment in 2020. After being disbanded, this group quietly formed Front Persaudaraan Islam (Neo-FPI) during COVID-19 and operated secretly through religious activities. The momentum of Neo FPI appeared publicly comes in 2022 when they took to the street for complaining the Minister of Religious Affairs’ comment of call for prayer, widely known as adzan. This study aimed at exploring how Neo-FPI responds and transforms after being dissolved constitutionally by the government and to what extent this rebirth is accepted by the Muslim community. The emergence of Neo-FPI can be interpreted by Sydney Tarrow (1998) as a puzzle of political opportunity. The social movement increased when it gained the support of resources and successfully mobilized the resource. The result of the study shows that the Neo-FPI might try to attempt on humanistic approach and moderation within the religious movement. However, substantially this group will not be different from the old version like an apple that falls not far from the tree.